ANALISIS “MARKETING 3.0” PADA PERUSAHAAN PT. RADIO SUARA INDRAKILA (KR RADIO 107,2 FM) YOGYAKARTA - Agung Sulistyo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The success of a company or establishment, cannot be separated from a variety of factors, both internal factors and external factors. Similarly, KR Radio, the radio station continues to exist conduct their activities using a variety of strategies. This study aims to determine the analysisMarketing Concept 3.0 at PT. Radio Voice Indrakila (KR Radio) Yogyakarta in the face of competition. According to Kotler, Kartajaya and Setiawan in a book entitled "Marketing 3.0" described, some of the concepts that make a company to be successful, both developed and developing are: First, the mission of the company to the consumer market. Second, the market value - the value of the company to employees. Third, market value - value of distribution partners. Fourth, market vision to shareholders. Fifth, to create sociocultural transformation. Sixth, create entrepreneurs in emerging markets. Seventh, conduct environmental conservation efforts. Based on research that has been done, PT. Radio Voice Indrakila (KR Radio) have not been able to apply all of the instruments of Marketing 3.0. In other words, PT. Radio Voice Indrakila not been able to become a successful company with Concept Marketing 3.0. Of 7 (seven) instrument must-have for success, PT. Radio Voice Indrakila only able to apply the 3 (three) instrument, namely: mission to the consumer market, to market value - value of distribution partners, and environmental conservation efforts. Keywords: Marketing 3.0, KR Radio Yogyakarta